1968
DOI: 10.1530/jrf.0.0150039
|View full text |Cite
|
Sign up to set email alerts
|

Daily Measurement of Pituitary Lh Content During Pregnancy in the Rat: Do Cyclic Changes Persist?

Abstract: Daily measurements of pituitary lh content during pregnancy in the rat, by the ovarian ascorbic acid depletion method, reveal no evidence of the regular changes manifested during the non-pregnant oestrous cycle. Instead, lh content rises from typical oestrous values on Day 1 to levels characteristic of cyclic pro-oestrus on Day 8. Pituitary lh content then exceeds pro-oestrous levels throughout the remainder of pregnancy until Day 21. Ovarian weight first decreases up to Day 10, then rises until the end of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
1

Year Published

1969
1969
1986
1986

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
(26 reference statements)
3
7
0
1
Order By: Relevance
“…A low tonic secretion of LH is assumed to cause this dioestrous follicular growth (Bogovich et al, 1981). It is not within the scope of this quantitative morphological study to discuss the hormonal situation in relation to follicular development in rats in the pregnant state, since this has already been extensively discussed by Schwartz & Tally (1968).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A low tonic secretion of LH is assumed to cause this dioestrous follicular growth (Bogovich et al, 1981). It is not within the scope of this quantitative morphological study to discuss the hormonal situation in relation to follicular development in rats in the pregnant state, since this has already been extensively discussed by Schwartz & Tally (1968).…”
Section: Discussionmentioning
confidence: 99%
“…During these prolonged dioestrous states inhibition of oestrus and ovulation occurs although enough evidence has been found to assume that follicular growth continues (Asami, 1920;Evans & Swezy, 1931;Ingram, 1962;Schwartz & Tally, 1968;Pedersen & Peters, 1971;Greenwald, 1978). However, there is still no agreement about the presence or absence of cyclic follicular maturation during these dioestrous periods.…”
Section: Introductionmentioning
confidence: 99%
“…The numbers of antral follicles were comparable to those found during the oestrous cycle until the 12th day of pregnancy, when their number increased sharply. A con¬ tinuous growth of follicles of all sizes is reported in the rat during pregnancy (Schwartz & Talley, 1968). Govan (1968Govan ( , 1970 (Krarup et al, 1969).…”
Section: During Pregnancymentioning
confidence: 97%
“…Other investigators have reported pituitary LH concentrations throughout pregnancy (Greenwald, 1966;Schwartz and Talley, 1968), pseudopregnancy (Schwartz and Rothchild, 1964) and on several isolated days of prolonged pseudopregnancy with hysterectomy (Labhsetwar, 1967;Christian, Yuan, and Rothchild, 1968), Their results obtained with the OAAD biossay are relatively similar to those presented here.…”
Section: Discussionsupporting
confidence: 87%